New experimentalism and computer-aided experiments - Leciejewski, Sławomir Grzegorz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2023)
In the 1980s, computer-aided experimental research became standard in the majority of leading research laboratories. Unfortunately, this shift was not adequately reflected in the professional literature related to the philosophy and methodology of science. A new experimentalism did emerge, aimed at adequately describing experimental practice (to be discussed in the first part of this article); however, in its initial phase, it failed to consider the role of computers in experimental research (discussed in the second part). This oversight by the philosophers of science, the proponents of the new experimentalism, is significant and calls for supplementation (addressed in the fourth part). By the turn of the 20th and 21st centuries, there were numerous philosophical analyses related to computer experiments, such as computer simulations. However, this article focuses only on classic experiments facilitated by various computer systems (e.g., LHC at CERN). In the final part of this article, I will present examples of aspects of experimental work that have not yet been analyzed and could potentially enhance new experimentalism with insights from computer-aided experiments.
Keywords: philosophy of experiment; computer-aided experimental practice; new experimentalism; research fields of the new experimentalism 2.0